PENGUATAN KOMPETENSI PEDAGOGIK GURU DI ERA MERDEKA BELAJAR MELALUI PENGEMBANGAN KEPROFESIAN BERKELANJUTAN DI SEKOLAH DASAR NEGERI 1 MUNCAR KABUPATEN TEMANGGUNG - Fidayati; Soedjono; I Made Sudana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
SDN 1 Muncar, Gemawang District has teachers who have good competence as the first winner in the differentiated teaching video competition. Other teachers still have difficulty understanding the characteristics of students from moral, social, emotional and intellectual aspects. Some teachers are weak in understanding how to learn and the teaching and learning process, teachers have not been able to develop the curriculum, senior teachers have difficulty using technology for learning purposes, some teachers are less effective in using the right language for students, and have difficulty finding differentiated learning content. The principal is tasked with developing teachers' pedagogical competence in Continuous Competence Development in the preparation of the RHK. The research method uses a qualitative descriptive approach. The research was conducted in the first semester of the 2024/2025 school year in July-November 2024. The research location was at SD Negeri 1 Muncar Temanggung. Data collection techniques were by interview, questionnaire and observation. Data validity test using triangulation technique. Data analysis using an interactive analysis model developed by Miles and Huberman. Research results: (1) Planning for continuous professional development in order to strengthen teacher pedagogical competence is carried out by compiling the teacher's Work Result Plan (RHK) on the Merdeka Mengajar Platform (PMM). This RHK helps teachers plan, implement, and evaluate learning activities, (2) Implementation of PKB in the preparation of teacher RHK can achieve the expected goals according to implementation priorities, (3) PKB reflection in order to strengthen teacher pedagogical competence: (a) implementation of RHK reflected in the learning community, in good condition, (b) RHK activities through reflection of achievements in participating in activities in RHK through PMM, IHT, webinars, in fairly good condition, (c) recommendations for implementing RHK when teachers carry out training, in good condition, (d) targets for implementing RHK in class, in very good condition; (4) PKB evaluation supports the development of the learning teacher profession (PPGP). Evaluation of the implementation of the PKB program to support teacher professional competence in the preparation of RHK, as follows: (a) results of RHK implementation, in the good category; (b) results of performance assessments in the implementation of RHK, in the good category, (c) recommendations for implementing RHK, in the fairly good category, (d) RHK implementation schedule, in the fairly good category. Suggestions from this study, with the preparation of RHK in the context of continuous professional development to strengthen good teacher pedagogical competence, it is necessary to recommend that teachers can carry out the preparation on the PMM platform independently and the principal strives for smooth internet access in schools.